Implementation of Restorative Justice in Resolving Domestic Violence Cases from the Perspective of Islamic Family Law (Mediation Study at the Lebong Police) - Pakhrizal Hakim; Rifanto Bin Ridwan; Hendriyanto Hendriyanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The implementation of restorative justice in resolving domestic violence (Kekerasan Dalam Rumah Tangga/KDRT) cases at the Lebong Resort Police has emerged as a significant issue within Indonesia’s contemporary law enforcement system. This approach provides an alternative mechanism for dispute resolution outside formal litigation by prioritizing reconciliation and the restoration of relationships between victims and perpetrators. Nevertheless, its application in domestic violence cases, which are categorized as absolute complaint offenses, raises important legal and ethical questions when examined through the lens of Islamic family law. Accordingly, this study seeks to analyze the practice of restorative justice at Polres Lebong and to evaluate its implementation from the perspective of Islamic family law. The research employs an empirical juridical method with a qualitative approach. Primary data were collected through in-depth interviews involving investigators from the Women and Children Protection Unit (Unit PPA) of Polres Lebong, victims, perpetrators, religious leaders, and community figures. In addition, secondary data were obtained from statutory regulations, academic books, and scholarly journal articles relevant to restorative justice and domestic violence issues. The findings reveal that the restorative justice process at Polres Lebong is primarily carried out through mediation involving the perpetrator, the victim, family members, and police officers. The process requires several essential conditions, including the perpetrator’s acknowledgment of wrongdoing, the victim’s willingness to forgive, and the formulation of a written peace agreement between the parties. From the standpoint of Islamic family law, this practice is closely aligned with the principle of iṣlāḥ (reconciliation), as reflected in QS An-Nisaʾ verse 35. The involvement of family representatives and community leaders in the mediation process also corresponds to the Islamic concept of appointing hakam (mediators) to resolve family disputes. Furthermore, agreements concerning compensation or financial support embody the Islamic values of justice (‘adālah) and responsibility (mas’ūliyyah). Even so, the implementation of restorative justice must continue to prioritize victim protection and ensure that reconciliation efforts do not compromise victims’ rights or create opportunities for repeated violence in the future.